The influence of online learning patterns on student awareness in education in the time of Covid-19 pandemic - Septian Aep Nugraha; Mansyur Srisudarso (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2023)
The online learning system is a learning system without face-to-face meetings between lecturers and students and is carried out online using the internet network. This is a quantitative research design and aimed at investigating whether there is an effect of online learning on students' awareness of learning amidst the Covid-19 pandemic. The research participants included all English literature students at STBA Bina Dinamika. This research begins by examining matters relating to the research variables and then providing questionnaires to respondents who are used as references. The data were then analyzed quantitatively. The results indicated that there is a contribution of perception to student awareness in doing assignments through online learning.